Application of POCIS for exposure assessment of munitions constituents during constant and fluctuating exposure. (30th March 2015) - Belden, Jason B.; Lotufo, Guilherme R.; Biedenbach, James M.; Sieve, Kristal K.; Rosen, Gunther
Abstract: The present study examined the potential use of polar organic chemical integrative samplers (POCIS) for exposure assessment of munitions constituents, including 2, 4, 6‐trinitrotoluene (TNT) and hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX), and their breakdown products (aminodinitrotoluenes [ADNTs], diaminonitrotoluenes [DANTs], and hexahydro‐1, 3, 5‐trinitroso‐1, 3, 5‐triazine [TNX]). Loss of munitions constituents from the sorbent phase after uptake was observed for the "pesticide" POCIS configuration but not for the "pharmaceutical" configuration. Therefore, the latter was selected for further investigation. Under constant exposure conditions, TNT, ADNTs, DANT, RDX, and atrazine (a common environmental contaminant) accumulated at a linear rate for at least 14 d, with sampling rates between 34 mL/d and 215 mL/d. When POCIS were exposed to fluctuating concentrations, analyte accumulation values were similar to values found during constant exposure, indicating that the sampler was indeed integrative. In contrast, caffeine (a common polar contaminant) and TNX did not accumulate at a linear rate and had a reduction in accumulation of greater than 50% on the POCIS during fluctuating exposures, demonstrating that POCIS did not sample those chemicals in an integrative manner. Moreover, in a flow‐through microcosm containing the explosive formulation Composition B, TNT and RDX were readily measured using POCIS, despite relatively high turnover rates and thus reduced water concentrations. Mean water concentrations estimated from POCIS were ± 37% of mean water concentrations measured by traditional grab sample collection. Thus, POCIS were found to have high utility for quantifying exposure to most munitions constituents evaluated (TNT, ADNTs, and RDX) and atrazine. Environ Toxicol Chem 2015;34:959–967. © 2014 SETAC